ANALISIS FAKTOR YANG MEMPENGARUHI MOTIVASI BIDAN DALAM PELAYANAN KB PASCA PERSALINAN PADA PROGRAM JAMINAN PERSALINAN DI PUSKESMAS KABUPATEN LUMAJANG - Herlidian Putri (Jurnal Kesehatan dr. Soebandi, 2014)
Postpartum birth control is one of the services or conditions for jampersal membership. In Lumajang, only 57.8% of jampersal participants participated in post-delivery family planning. During this time midwives tend not to do family planning counseling in depth, so it is assumed that midwife motivation in family planning services after delivery is low. The purpose of this study is to determine the factors that influence the motivation of midwives in post-delivery family planning services in the jampersal program. This research is an observational study with cross-sectional design. Data was collected in a questionnaire using a structured questionnaire. Population are all midwives who are obliged to carry out jampersal in Lumajang Regency. The number of respondents was 164 Midwives who were selected by clustered random sampling. Bivariate analysis was performed with Chi square test and multivariate with logistic regression. The results showed that the majority (78.7%) of respondents had a Diploma III education, had a tenure of> 10 years (57.9%) and (54.9%) aged> 35 years. Most respondents (56.1%) have low motivation. Respondents' perceptions of jobs, incentives, supervision techniques, and administrative policies are mostly good. Midwives' responsibilities and competencies are mostly good. There is a positive relationship between responsibilities, perceptions of supervision techniques, perceptions of administrative policies and midwives' motivation in post-delivery family planning services. There is no relationship between perceptions of work, perceptions of incentives, competencies and motivation in family planning services after delivery. The most dominant variable influencing midwife motivation in family planning services after delivery to Jampersal is responsibility. It is recommended that the Health Office provide a format for post-delivery family planning reporting, the supervision of the jampersal program and simplify the claim process.